The Pattern of Microwave Scattering by the Dielectric of Milks - Nugroho, Agung Tjahjo; Sa’adah, Nurul; Cahyono, Bowo Eko (Universitas Jember, 2022)
A microwave electric field scattering by a dielectric object had been developed to identify the type of a milk. A simple geometric tomographic system is applied. The milk is placed in a cylindrical tube and emitted with a microwave signal which is described in term of a harmonic function. The scattering field anywhere outside the cylinder is quantifed analitycaly in which the unknown coefecients of the analytic function are determined at the surface of the cylinder. Three different type of milks, whole milk, UHT, and skim milk are studied. The incident fields are scanned from 1 GHz to 20 GHz and the scattering fields due to the illumination are quantified in three different locations around the objects. The study shows that the scattering field pattern depent on the the type of the milk. The whole milk produces the lowes and highest magnitude of the scattering field at 2.4 GHz and 4.5 GHz respectively. These frequency points are higher that that produce by the UHT and skim milk.